2011
DOI: 10.1378/chest.10-1872
|View full text |Cite
|
Sign up to set email alerts
|

Wrist Actigraphy

Abstract: To record sleep, actigraph devices are worn on the wrist and record movements that can be used to estimate sleep parameters with specialized algorithms in computer software programs. With the recent establishment of a Current Procedural Terminology code for wrist actigraphy, this technology is being used increasingly in clinical settings as actigraphy has the advantage of providing objective information on sleep habits in the patient's natural sleep environment. Actigraphy has been well validated for the estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
419
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(435 citation statements)
references
References 77 publications
(31 reference statements)
6
419
0
10
Order By: Relevance
“…39 Our work is most similar to a recent report by Tsai et al 25 with regard to the average number of self-reported naps observed in 41 third-trimester frequent nappers (6.80 ± 2.97) as well as the reduction in TST. We somewhat agree with their suggestion that napping might interfere with subsequent nighttime sleep quantity, and that it does not compromise subsequent nighttime sleep continuity.…”
supporting
confidence: 91%
“…39 Our work is most similar to a recent report by Tsai et al 25 with regard to the average number of self-reported naps observed in 41 third-trimester frequent nappers (6.80 ± 2.97) as well as the reduction in TST. We somewhat agree with their suggestion that napping might interfere with subsequent nighttime sleep quantity, and that it does not compromise subsequent nighttime sleep continuity.…”
supporting
confidence: 91%
“…Actimetry is a noninvasive method in which trials were performed with a high sample with these kinds of assays and gives enough information to evaluate if a diet improves activity/inactivity circadian rhythm (Adamec et al 2010;Ancoli-Israel et al 2003). Wrist actimetry is a well-validated technique to study nocturnal sleep, as referenced elsewhere (Martin and Hakim 2011). This method has been used to determine disturbances in actual sleep time, sleep efficiency, sleep latency, wake bouts, and sleep fragmentation index in elderly people (Huang et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…4 The Actiwatch2 (Philips Respironics, Oregon, United States) is a widely used actigraph worn on the nondominant wrist that has the capability to determine sleep and wake patterns. 5 It has been validated against PSG in healthy children 6 and adults. 3 Sleep parameters can be derived from Actiwatch2 recordings using three different threshold settings (low, medium, or high) for detection of wake-related accelerations (movements) before…”
Section: Introductionmentioning
confidence: 99%